Parents’ Perception on the Implementation of Home Learning during Covid-19 - Ifoni Ludji; Tiarma Marpaung (Jurnal Basicedu, 2021)
This study aimed to describe the parents’ perception on the benefits and challenges towards home learning during the pandemic. Descriptive qualitative study taking a case in two elementary schools in Kupang, East Nusa Tenggara. There were 20 parents from both schools taken purposively as the sample. 20 questions posted on Google Form as the instrument. The results showed that the implementation of home learning brought two perceptions on the benefits and challenges. The benefits were regarding to possibility of home learning to provide an individualized experience and flexibility system of education, to minimize the possibility of the kids to get infected by the Covid-19, to intimate relationship between the kids and parents, to enforce as well as boost the parents’ digital literacy as well as creativity in carrying out the learning material. Further perception mentioned that the implementation of home learning also brought certain challenges to those parents such as, requiring more expenses to buy the internet quota, causing the kids less motivated and overwhelming in learning, raising the work load of the parents, time inefficiency for working parents by spending more time to assist the kids during the learning, increasing the tense between the kids and parents during the learning.